Navigating the Legal Landscape: Evaluating the Case for Artificial Intelligence as Juristic Persons - Jose, Nandu Sam (Indian Journal of Computer Science, 2023)
The rapid development of Artificial Intelligence (AI) has sparked an ongoing debate regarding the inclusion or exclusion of AI systems within the notion of juristic personality. This article explores the concept of juristic personality, its application to AI systems, and the potential implications and challenges of recognizing AI as a juristic person. It discusses the arguments for and against granting juristic personality to AI systems, touching upon issues such as functional capabilities, accountability, and moral agency. Additionally, the article examines proposed models of AI juristic personality, as well as alternative approaches to AI regulation that do not involve granting juristic personality. The analysis highlights the complexity of the debate, emphasizing the need for a careful assessment of the potential impacts on society, the economy, and the legal system. By engaging in a comprehensive and nuanced dialogue, stakeholders can develop appropriate legal and regulatory frameworks to address the challenges posed by AI while upholding the fundamental values of justice, fairness, and human dignity.